2010
DOI: 10.1371/journal.pone.0013141
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Calcium Regulates the Retrotranslocation of Trypanosoma Cruzi Calreticulin to the Cytosol

Abstract: For most secretory pathway proteins, crossing the endoplasmic reticulum (ER) membrane is an irreversible process. However, in some cases this flow can be reversed. For instance, misfolded proteins retained in the ER are retrotranslocated to the cytosol to be degraded by the proteasome. This mechanism, known as ER associated degradation (ERAD), is exploited by several bacterial toxins to gain access to the cytosol. Interestingly, some ER resident proteins can also be detected in the cytosol or nucleus, calretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Experiments aimed at quantifying the association of GPI-minus reporters with BiP and/or other molecular chaperones may shed some light on this issue. In this line, however, it is worth noting that calreticulin, the main N-glycoprotein chaperone in T. cruzi (35), does not seem to play a significant role in apo-mucin maturation/trafficking, as revealed by the A66 mutant. Further evidence weigh against "quality control" as a mechanism for regulating export of ⌬GPI reporters.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Experiments aimed at quantifying the association of GPI-minus reporters with BiP and/or other molecular chaperones may shed some light on this issue. In this line, however, it is worth noting that calreticulin, the main N-glycoprotein chaperone in T. cruzi (35), does not seem to play a significant role in apo-mucin maturation/trafficking, as revealed by the A66 mutant. Further evidence weigh against "quality control" as a mechanism for regulating export of ⌬GPI reporters.…”
Section: Discussionmentioning
confidence: 88%
“…As for the molecular basis underlying this observation, two alternative hypotheses can be envisaged. On one hand, it is possible that ⌬GPI reporters, which are normally membrane bound, are unable to attain a stable conformation when expressed in soluble form and are thus retained in the ER by folding quality control systems (35). Experiments aimed at quantifying the association of GPI-minus reporters with BiP and/or other molecular chaperones may shed some light on this issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Afshar et al (24) claimed that cyt-CRT is not a proteasomal substrate because it did not detect ubiquitinated cyt-CRT in cells. On the other hand, Labriola et al (25) suggested that CRT is degraded in the cytosol by proteasome because, after exposure of cells to an inhibitor of ER Ca 2ϩ -ATPase, cyt-CRT level was reduced by CHX treatment and increased by MG132 treatment. Our present findings indicate that both CRT and R-CRT are proteasomal substrates, although the degradation rate of R-CRT is lower than that of CRT (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant subset of proteins displays ubiquitination-independent turnover (21), which is not surprising in view of the co-existence of several types of proteasomal complexes in eukaryotic cells (22). The possible role of CRT as a substrate for proteasomal degradation is controversial (23)(24)(25). The degradation mechanism of R-CRT remains unknown.…”
mentioning
confidence: 99%